Protein plasticity underlines activation and function of ATP-independent chaperones - Reichmann, Dana; Suss, Ohad (Frontiers in Molecular Biosciences, 2015)
One of the key issues in biology is to understand how cells cope with protein unfolding caused by changes in their environment. Self-protection is the natural immediate response to any sudden threat and for cells the critical issue is to prevent aggregation of existing proteins. Cellular response to stress is therefore indistinguishably linked to molecular chaperones, which are the first line of defense and function to efficiently recognize misfolded proteins and prevent their aggregation. One of the major protein families that act as cellular guards includes a group of ATP-independent chaperones, which facilitate protein folding without the consumption of ATP. This review will present fascinating insights into the diversity of ATP-independent chaperones, and the variety of mechanisms by which structural plasticity is utilized in the fine-tuning of chaperone activity, as well as in crosstalk within the proteostasis network. Research into this intriguing class of chaperones has introduced new concepts of stress response to a changing cellular environment, and paved the way to uncover how this environment affects protein folding.